Digital Content Security by Butterfly and Elliptic Curve Cryptography with Channel Optimization - Kartikey Pandey; Deepmala Sharma (International Journal of Mathematical, Engineering and Management Sciences)
As more and more services and solutions are utilizing digital data, it becomes imperative to provide strong security mechanisms to safeguard sensitive content with a rapidly growing number of users. This is especially important for users who are not as techie, and thus do not have the knowledge or skill to implement their own protections. To this effect, the present paper proposes a new model for image validation at the receiver side. This model works on low bandwidth channel and provides same level of security as end-to-end encryption. The security of the images is realized by using elliptic curve cryptography (ECC), while the segmentation and discrete wavelet transform (DWT) cooperate for achieving both transmission efficiency and preservation of individual pixel data. The model utilizes watermark embedding and a butterfly selection method for image authentication. This involves a cognitive decision step thereby ensuring the highest possible effectiveness for integrity verification. Experiments on a standard image dataset show that the proposed model is able to be much more robust under different attack vectors.